Sustainable Teacher Training and SDGs Knowledge: A Study from the Reading Perspective - Eduardo Encabo-Fernández; Marina Maestre-Espinosa; Isabel Jerez-Martínez; Lourdes Hernández-Delgado (MDPI AG, 2023)
This study aims at analysing the relevance of the Sustainable Development Goals (SDGs) in initial teacher education and the prominence given to reading, as well as the relationship between the two issues. The research modality chosen is non-experimental, descriptive (survey) and mixed. On the one hand, a questionnaire designed for 118 students of the different teaching-related degrees offered at the Faculty of Education of Universidad de Murcia (Spain) was used to collect information. On the other hand, the interview script was prepared for five professors from the University who teach in these degrees or postgraduate studies, also related to teaching. The results highlight the poor treatment and general lack of knowledge about the SDGs and the little consideration given to them in the literature. There is a pressing need to change the approach and to advocate for a cross-cutting approach to both issues, also taking advantage of the relationship between literature and SDGs for the benefit of the education community.